1993
DOI: 10.14430/arctic1356
|View full text |Cite
|
Sign up to set email alerts
|

Plant Activity under Snow and Ice, with Particular Reference to Lichens

Abstract: ABSTRACT. In polar ecosystems primary producers have to cope with the very limited living conditions of the harsh climate. Vascular plants in the Northern Hemisphere extend to the northem-most edges of the continents, but only two taxa are present as far south as the Antarctic Peninsula region in the Southern Hemisphere. Lower plants, lichens in particular, become more important with increasing latitudes and form the dominant element of the Antarctic vegetation. Based on recent investigations and literature, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…High resistance of lichens from polar regions to partial dehydration of thalli and maintenance of photosynthetic processes is well known and reported (e.g. Kappen 1993, Kappen et al 1995, Henri 2011, Jupa et al 2012, Wu et al 2012, Barták 2014). An interesting effects was observed on August 9 th -10 th , when a dramatic decrease of Φ PSII was found and related to a decrease in air temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High resistance of lichens from polar regions to partial dehydration of thalli and maintenance of photosynthetic processes is well known and reported (e.g. Kappen 1993, Kappen et al 1995, Henri 2011, Jupa et al 2012, Wu et al 2012, Barták 2014). An interesting effects was observed on August 9 th -10 th , when a dramatic decrease of Φ PSII was found and related to a decrease in air temperature.…”
Section: Discussionmentioning
confidence: 99%
“…They also show extremely high dehydration and freezing tolerance, and maintenance of full photosynthetic capacity over a wide range of partial dehydration and thallus temperature. (Kappen 1993).In this study, attention is devoted to the comparison of lichen and BSCs photosynthetic activities in relation to environmental factors. To assess of physiologic activity of tested species, we used monitoring of daily changes in Φ PSII .…”
Section: Introductionmentioning
confidence: 99%
“…There 241 were no abundance differences for Collembola and Acari between control plots and OTCs in 242 the moss community (Table 4). itself resulting from the increased insulation and higher temperatures provided by the deeper 298 snow pack (Kappen 1993). Therefore, it is possible that the same mechanism, carbon depletion 299 due to increased winter respiration, also affected U. antarctica inside the OTCs, a proposition 300 which is supported by the CO2 calculations.…”
Section: Response Of the Moss Community To Warmingmentioning
confidence: 99%
“…The possibility of activation by water vapour alone is controversial for lichens in Antarctica. It has been experimentally demonstrated that some Antarctic lichens can reactivate from water vapour alone (Kappen, 1993) and Schroeter and Scheidegger (1995) showed the Antarctic lichen Umbilicaria aprina Nyl. being activated by water uptake in the gaseous phase from snow at subzero temperatures.…”
Section: Photosynthetic Performancementioning
confidence: 99%